Des mots des femmes: rencontres linguistiques Actes de la journée d'étude tenue à l'Université de Florence (1er décembre 2006) - FARINA, ANNICK; RAUS, Rachele (Atti, 2007)
To retrace the history of women's words, taken or given, their presence and their influence at the different periods of our history, in French-speaking literary and journalistic discourse, in the reference works that are dictionaries and encyclopedias, a variety of perspectives have been brought together, by specialists from different Countries and different scientific backgrounds. How do women fit into the definition of a language standard and into linguistic creation? What are the words that describe them or used to address them? Who are the female figures that emerge from the various works analyzed, vectors of our cultures and societies? From the mistress or the foreigner, the intellectual or the whore, the factory worker or the woman of power, different facets of women, exposed in their intentions or their intimacies, offer a dynamic vision of the female condition.